PENGARUH MANAJEMEN PENGETAHUAN TERHADAP KINERJA ORGANISASI DENGAN VARIABEL KOMITMEN DAN KEWIRAUSAHAAN SEBAGAI VARIABEL INTERVENING PADA KECAMATAN DI LINGKUNGAN KOTA PEKANBARU - Shauma Fajri; Zulfadil Zulfadil; Rosyetti Rosyetti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the direct effect of knowledge management on organizational performance. To analyze the influence of commitment to the organization. To analyze the effect of entrepreneurship on organizational performance. To analyze the indirect effect of knowledge management mediated by commitment to organizational performance. To analyze the indirect effect of knowledge management mediated by entrepreneurship on organizational performance. In this study, the population in this study were 108 employees from 12 subdistricts in Pekanbaru City and the sample to be used was 90 people. The data used in this study are primary data and secondary data and the data collection method is a questionnaire. The data analysis technique used in this study is SEM. The results of knowledge management research affect commitment, entrepreneurship and organizational performance. Commitment has a positive and significant influence on organizational performance. Entrepreneurship influences organizational performance. Knowledge management influences organizational performance through organizational commitment as an intervening variable. Knowledge management influences organizational performance with organizational commitment as an intervening variable.